Pemanfaatan Media Interaktif Bahasa Arab Berbasis Constract 2 Untuk Meningkatkan Kemahiran Membaca Siswa Kelas 7 MTs/SMP - Ahsanuddin, Mohammad; Moh. Ainin; Moh. Fauzan; Abd Rauf Hassan; Muhammad Ahsan Thoriq; Farika Riskiyah; Rico Fenda Pradana; Arya Wahyu Pratama (Singular: Journal of Pedagogical Language, Literature, and Cultural Studies, 2024)
This study aimed to enhance the reading proficiency of seventh-grade students at MTs/SMP through the use of interactive Arabic learning media based on Construct 2. Using a classroom action research approach, the study involved 15 students from Grade 7 at SMP Darul Faqih, with the teacher serving as an observer. The research was conducted in two cycles, with data showing that students' average score in the first cycle was 40, falling below the minimum competency standard (MCS). However, in the second cycle, the average score improved significantly to 80, indicating a substantial increase in reading proficiency. These results highlight that the use of Construct 2-based interactive media effectively supports students' learning, particularly in developing their reading skills in Arabic. Thus, it can be concluded that this media is a valuable tool for enhancing students' Arabic language learning outcomes.